2022
DOI: 10.1002/ange.202117658
|View full text |Cite
|
Sign up to set email alerts
|

Logical Analysis of Multiple Single‐Nucleotide‐Polymorphisms with Programmable DNA Molecular Computation for Clinical Diagnostics

Abstract: Analyzing complex single‐nucleotide‐polymorphism (SNP) combinations in the genome is important for research and clinical applications, given that different SNP combinations can generate different phenotypic consequences. Recent works have shown that DNA‐based molecular computing is powerful for simultaneously sensing and analyzing complex molecular information. Here, we designed a switching circuit‐based DNA computational scheme that can integrate the sensing of multiple SNPs and simultaneously perform logical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In recent decades, it has been widely confirmed that biocomputing could offer intelligent and subtle solutions to both computing tasks and disease diagnostics. 56,57 Specifically, Fan et al proposed the concept of a DNA "contrary logic pair" (CLP) to try to reduce the time/cost of molecular computing based on functional nucleic acids. [58][59][60] After that, electrochemical and electro-chemiluminescent CLPs were further fabricated.…”
Section: Contrary Logic Pairs Based On the Fe 3 Ni-mof-nh 2 Nanozymementioning
confidence: 99%
“…In recent decades, it has been widely confirmed that biocomputing could offer intelligent and subtle solutions to both computing tasks and disease diagnostics. 56,57 Specifically, Fan et al proposed the concept of a DNA "contrary logic pair" (CLP) to try to reduce the time/cost of molecular computing based on functional nucleic acids. [58][59][60] After that, electrochemical and electro-chemiluminescent CLPs were further fabricated.…”
Section: Contrary Logic Pairs Based On the Fe 3 Ni-mof-nh 2 Nanozymementioning
confidence: 99%
“…As represented in this report, oligonucleotide biomarkers, such as miRNA, can be used as inputs in DNA computation. Diagnostic applications are therefore an emerging trend in the development of medical DNA computation, 208,209 holding the promise of substantial impacts on the advancement of medical molecular robotics. Furthermore, the above DNA-based neural network architectures offer the fascinating prospect of endowing molecular robots with 'intelligence', including the realisation of intricate human-brain-like functionalities from perception to memory and consciousness, using DNA.…”
Section: Dna Computingmentioning
confidence: 99%